Liver transplantation for hepatocellular carcinoma beyond the Milan criteria. Issue 6 (24th March 2015) - Xu, Xiao; Lu, Di; Ling, Qi; Wei, Xuyong; Wu, Jian; Zhou, Lin; Yan, Sheng; Wu, Liming; Geng, Lei; Ke, Qinghong; Gao, Feng; Tu, Zhenhua; et al.
Abstract : Objective: Liver transplantation is an optimal radical therapy for selected patients with hepatocellular carcinoma. The stringent organ allocation system driven by the Milan criteria has been challenged by alternative sets of expanded criteria. Careful analysis is needed to prove that the Milan criteria can be expanded safely and effectively. Design: This study collectively reviewed 6012 patients of hepatocellular carcinoma from the China Liver Transplant Registry. Expanded criteria were evaluated to characterise an optimised expansion with acceptable outcomes beyond the Milan criteria. Results: Compared with the Milan criteria, Valencia, University of California, San Francisco, University Clinic of Navarra and Hangzhou criteria provided an expansion of 12.4%, 16.3%, 19.6%, and 51.5%, respectively. The post-transplant survivals of patients fulfilling the expanded criteria were comparable to that of the Milan criteria. The analysis of net reclassification improvement and area under the receiver operating characteristic curves showed an excellent efficiency in recurrence prediction for the expanded criteria compared with the Milan criteria. In patients exceeding Milan but fulfilling the Hangzhou criteria (N=1352), α-fetoprotein (AFP) >100 ng/mL and tumour burden>8 cm were the only two independent prognostic factors (p<0.001). Accordingly, the Hangzhou criteria were stratified as type A (tumour burden ≤8 cm, or tumour burden >8 cm but AFP≤100 ng/mL) and type B (tumour burden >8 cm but AFP between 100 and 400 ng/mL). Type A showed significantly higher 5-year tumour-free survival rates compared with type B (p<0.001). Conclusions: The Milan criteria can be expanded safely and effectively. The prognostic stratification system based on the Hangzhou criteria serves as a hierarchy of transplant candidates for hepatocellular carcinoma.